2020
DOI: 10.18632/aging.102797
|View full text |Cite
|
Sign up to set email alerts
|

Obg-like ATPase 1 (OLA1) overexpression predicts poor prognosis and promotes tumor progression by regulating P21/CDK2 in hepatocellular carcinoma

Abstract: Background: Obg-like ATPase 1 (OLA1) has been found to have a dual role in cancers. However, the relationship between OLA1 and hepatocellular carcinoma (HCC) remains unclear. Results: High expression of OLA1 in HCC was detected in public datasets and clinical samples, and correlated with poor prognosis. Downregulation of OLA1 significantly inhibited the proliferation, migration, invasion and tumorigenicity of HCC cells. Mechanistically, GSEA showed that OLA1 might promote tumor progression by regulating the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 44 publications
5
32
0
Order By: Relevance
“…Sun et al [7] indicated that OLA1 (DOC45) mRNA was overexpressed in cancers of the colon, rectum, stomach, ovary, uterus and lung, and the elevated expression of OLA1 protein was con rmed in colon cancer tissues. As consistent with our results, Huang et al [15] reported that OLA1 was highly expressed in hepatocellular carcinoma, and correlated with unfavorable clinical characteristics like tumor size, portal vein tumor thrombus and TNM stage, and predicted poor survival. Bai et al [9] found that OLA1 expression was signi cantly higher in lung cancer tissues than that in paired normal lung tissues.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Sun et al [7] indicated that OLA1 (DOC45) mRNA was overexpressed in cancers of the colon, rectum, stomach, ovary, uterus and lung, and the elevated expression of OLA1 protein was con rmed in colon cancer tissues. As consistent with our results, Huang et al [15] reported that OLA1 was highly expressed in hepatocellular carcinoma, and correlated with unfavorable clinical characteristics like tumor size, portal vein tumor thrombus and TNM stage, and predicted poor survival. Bai et al [9] found that OLA1 expression was signi cantly higher in lung cancer tissues than that in paired normal lung tissues.…”
Section: Discussionsupporting
confidence: 93%
“…With regard to the biological role of OLA1 in cancer cells, it is also still controversial. In hepatocellular carcinoma, downregulation of OLA1 signi cantly inhibited the proliferation, migration, invasion and tumorigenicity of hepatocellular carcinoma cells [15]. On the contrary, recent study on oral carcinoma revealed that knockdown OLA1 enhanced cell migrative ability, but have no effect on cell proliferation [10].…”
Section: Discussionmentioning
confidence: 97%
“…At the same time, the AUC value of the signature-based nomogram was nearly better than the AUC values of age, grade status and stage in 1-, 3, 5-years. Next, we further veri ed the mRNA expression of 6-genes (RBM45, PSMD1, OLA1, CCT6A , LCAT and IVD) for HCC patients in the Oncomine, TIMER, TCGA and ICGC database, which is consistent with the results of previous studies (18)(19)(20)(21). What's interesting, there are no reports of RBM45 and IVD genes in liver cancer.…”
Section: Discussionsupporting
confidence: 87%
“…Upregulation of OLA1 is observed in various cancers, 63 and is associated with poor prognosis in breast and hepatocellular carcinomas 64,65 . Although OLA1 has ATPase or GTPase activity and contributes to stress responses in cells, 64,66 the precise role of OLA1 in carcinogenesis remains to be elucidated.…”
Section: Roles Of Brca1 In Centrosome Regulationmentioning
confidence: 99%